Development of Community TB-Screening Unit for New TB Patient Detection by Using TB-Lamp in Health Region 7, Thailand: the Medical Science Innovation for the Innovative Healthcare Management - มหาโยธา, อธิชา; สมบัติธีระ, สุทธิกานต์; บุญพุด, นุชจรี; Set-on, Thanongsak; ช่างทอง, วัจนา; ฤดีอเนกสิน, จณิศรา; ลัภนะกุล, พรทิพย์ (Journal of Health Science of Thailand, 2023)
The objective of this study was to develop potential on TB testing laboratories at community hospitals in Health Region 7 to enhance the capacity of TB screening by using the TB-LAMP method with the aims to proactively detect new TB patients in the area as well as to support a rapid mission to solve TB problems in the region by transferring the DMSc TB FastAmp Kit innovation to laboratories at community hospitals that were able to provide the services. There were three phases of operation consisting of: (1) a pilot study that evaluated the DMSc TB FastAmp Kit compared to the existing method of AFB staining, (2) development of a prototype of TB-LAMP laboratories at a community level, and (3) expansion of community-based TB-LAMP laboratories to cover the whole area. Based on the preliminary evaluation, the results indicated that the TB-LAMP method using the DMSc TB FastAmp Kit could be utilized for TB screening due to its great sensitivity and increased detection rate in the negative smear-AFB samples as high as 28.8%. Furthermore, when it was applied to the prototype of community hospitals, the efficiency detection by TB-LAMP was utilized for the detecting new TB patients increased by 10.2%\. This outcomes had resulted in double detection of new TB patients as compared to the original method. In addition, the innovation had accelerated district-level TB problem resolutions, as well as the expansion of TB screening units using the TB-LAMP method in community hospitals to support the expansion of the implementation. Additionally, it was convenient for the public to undergo screening in the vicinity of their homes for TB early detections and rapid treatment.